2007
DOI: 10.1111/j.1440-1746.2006.04758.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors reflecting the pathological severity of non‐alcoholic fatty liver disease: Comprehensive study of clinical and immunohistochemical findings in younger Asian patients

Abstract: BMI could be used to distinguish NASH from steatosis in younger Korean patients. A high BMI with a low alanine aminotransferase (ALT) value tended to suggest the presence of severe fibrosis in NASH, while the number of CD68+ Kupffer cells and the staining intensity of TNF-alpha and UCP-2 were correlated with general pathologic severity in patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
65
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 36 publications
9
65
0
3
Order By: Relevance
“…Interestingly, we found that the number of liver resident CD163 + Kupffer cells increased in children with NASH and correlated with severity of disease. These results fit well with previous studies suggesting that Kupffer cell activation is a causal factor for hepatic damage in NASH (14)(15)(16). Furthermore, our recent data indicated that the hepatic expression of CD163 + cells is increased in a rodent model of diet-induced NAFLD (43).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, we found that the number of liver resident CD163 + Kupffer cells increased in children with NASH and correlated with severity of disease. These results fit well with previous studies suggesting that Kupffer cell activation is a causal factor for hepatic damage in NASH (14)(15)(16). Furthermore, our recent data indicated that the hepatic expression of CD163 + cells is increased in a rodent model of diet-induced NAFLD (43).…”
Section: Discussionsupporting
confidence: 81%
“…This is important, as we hypothesized that patients with an increase in transaminases may present NAFLD, yet, as observed in this study, almost half of the patients with NAFLD had normal transaminase values. This has important clinical repercussions, as shown in studies based on liver biopsy in which patients with NAFLD and normal transaminases present severe lesions [27,28]. This is why several authors have proposed that the value of normality of ALT be redefined to improve its sensitivity [8,26,29,30].…”
Section: Discussionmentioning
confidence: 94%
“…This is achieved by a slightly enhanced respiration and a subsequently reduced oxygen tension and shortened lifetime of ubiquinone anion radical (Jezek et al, 2004). Adaptive mechanisms to oxidative stress were also reported for livers of patients with NASH (Perlemuter et al, 2005;Park et al, 2007). Mitochondria obtained from patients with NASH were confirmed to display UCP-2 expression, elevated ROS level and increased levels of lipid peroxidation products (Serviddio et al, 2008a).…”
mentioning
confidence: 88%
“…It is noteworthy that although oxidative DNA damage occurs already at early stages of steatohepatitis, up-regulation of adaptive antioxidant mechanisms preserved the viability of hepatocytes in vitro (Cortez-Pinto et al, 1999;Rashid et al, 1999;Diehl, 2005). It was demonstrated that induction of the mitochondrial UCP-2, which is a possible cellular mechanism to adapt to ROS and to prevent apoptosis by uncoupling the oxidative phosphorylation, caused enhanced susceptibility of hepatocytes to other stressors, such as hypoxia, TNF-␣, or carbon tetrachloride-induced toxicity (Cortez-Pinto et al, 1998;Yang et al, 2000;Garcia-Ruiz and Fernandez-Checa, 2006;Donthamsetty et al, 2007;Park et al, 2007). Activation of UCP-2 by FA hydroperoxides, which are products of lipid peroxidation, is thought to be part of a negative feedback mechanism to reduce intracellular ROS (Jezek et al, 2004).…”
mentioning
confidence: 99%